The Surface Properties of Calcite: An Adsorption Model with Orbital Control - Nikolai V. Nikolenko (Adsorption Science & Technology)
The energies of unoccupied and occupied orbitals were used as the correlation parameters between the electronic and adsorptive properties of organic molecules. A model describing the chemisorption of organic compounds on CaCO 3 involving two types of interaction, i.e. two-electron, donor–acceptor interaction HOMO(adsorbent) → LUMO(adsorbate) and four-electron, three-orbital interaction HOMO(adsorbent) → {LUMO(adsorbate) + HOMO(adsorbate)}, was proposed. It was concluded that strengthening of the bond involved in chemisorption occurred if the energies of the occupied orbitals associated with the adsorbate and adsorbent were concurrent.